Development and validation of a rapid turbidimetric assay to determine the potency of cefuroxime sodium in powder for dissolution for injection - Vieira, Daniela C. M.; Fiuza, Thalita F. M. [UNESP]; Salgado, Hérida R. N. [UNESP] (Pathogens, 2014)
The cefuroxime sodium is a second generation cephalosporin indicated for infections caused by Gram-positive and Gram-negative microorganisms. Although this drug is highly studied and researched regarding the antimicrobial activity, pharmacokinetics and pharmacodynamics, there are few studies regarding the development of analytical methodology for this cephalosporin. Thus, research involving analytical methods is essential and highly relevant to optimize its analysis in the pharmaceutical industry and guarantee the quality of the product already sold. This study describes the development and validation of a microbiological assay applying the turbidimetric method for the determination of cefuroxime, using Micrococcus luteus ATCC 9341 as micro-organism test and 3x3 parallel line assay design, with nine tubes for each assay, as recommended by the Brazilian Pharmacopoeia. The developed and validated method showed excellent results of linearity, seletivity, precision and robustness, in the concentration range from 30.0 to 120.0 mg/mL, with 100.21% accuracy and content 99.97% to cefuroxime sodium in injectable pharmaceutical form.
Keywords: Cefuroxime sodium; Microbiological testing; Quality control; Validation and stability